Sonic Pi – performance in education, technology and art. Issue 2 (2nd July 2016) - Aaron, Sam
ABSTRACT: Sonic Pi is a live coding language and performance environment with two specific and distinct goals: firstly, to facilitate the teaching of programming within schools and secondly, to enable artists to deliver virtuosic live coded music performances. This article considers the implications of prioritising performative elements within education. Is it the case that the act of education can be treated as a performance? If so, what knowledge and learning could a focus on performance enable us to share across the seemingly disparate contexts of education, technology and art?